Fecal microbiota profiling in irritable bowel syndrome and inflammatory bowel disease patients with irritable bowel syndrome-type symptoms - Xiufang Cui (BMC, 2021)
Abstract Background The intestinal microbiota is thought to be involved in the occurrence of inflammatory bowel disease in remission with irritable bowel syndrome (IBS)-type symptoms, but the specific distinct profile of these bacteria remains unclear. This cross-sectional study aims to investigate the fecal microbiota profiling in patients with these diseases. Methods Fecal samples from 97 subjects, including Crohn’s disease patients in remission with IBS-type symptoms (CDR-IBS+) or without IBS-type symptoms (CDR-IBS−), ulcerative colitis patients in remission with IBS-type symptoms (UCR-IBS+) or without IBS-type symptoms (UCR-IBS−), IBS patients and healthy controls, were collected and applied 16S ribosomal DNA (rDNA) gene sequencing. The V4 hypervariable regions of 16S rDNA gene were amplified and sequenced by the Illumina MiSeq platform. The differences in the sample diversity index in groups were analyzed with R software. Results The richness of the intestinal microbiota in the CDR-IBS group was markedly lower than those in the control and IBS groups based on the analysis of observed species and the Chao index (P < 0.05). The observed species index in the CDR-IBS+ group was higher than that in the CDR-IBS− group (median index: 254.8 vs 203, P = 0.036). No difference was found in alpha diversity between UCR patients with IBS-type symptoms and those without related symptoms. At the genus level, the number of Faecalibacterium in CDR patients with IBS-type symptoms increased significantly, while Fusobacterium decreased versus those without such symptoms (mean relative abundance of Faecalibacterium: 20.35% vs 5.18%, P < 0.05; Fusobacterium: 1.51% vs 5.2%, P < 0.05). However, compared with the UCR-IBS− group, the number of Faecalibacterium in the UCR-IBS+ group decreased, while the number of Streptococcus increased, but there was no significant difference in the genus structure. The abundance and composition of the microbiota of IBS patients were not distinct from those of healthy controls. Conclusions The IBS-type symptoms in CD patients in remission may be related to an increase in Faecalibacterium and a decrease in Fusobacterium. The IBS-type symptoms in UC patients in remission cannot be explained by changes in the abundance and structure of the intestinal microbiota.